Organisational capital: The power of an economic metaphor ; organisational capital in German establishments - Dieter Sadowski; Oliver Ludewig (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2003)
The concept of organisational capital is multifaceted and often inadequately demarcated from related concepts like human or social capital. We define organisational capital as an agglomeration of technologies - business practices, processes and designs - that enable firms to gain a sustainable competitive advantage. Since organisational practices and their combinations are the primary components of organisational capital, it is inseparably linked to the organisation, which distinguishes it from other types of capital. Organisational capital is predominantly non-tangible, non-fungible and idiosyncratic; therefore it is hard to measure. Measuring it by using additive indices of different practices or system variables presumes a concrete functional form for the link between organisational practices and the level of organisational capital, which is in reality unknown. Following an operationalisation of Lev and Radhakrishnan (2003) we approximate the level of specific organisational capital, using the data of the IAB-establishmentpanel to control for several influencing variables. Unlike Lev and Radhakrishnan, we control for the effects of human and social capital and hence isolate the effects of organisational capital.
Keywords: 330; organisation; organisational capital; corporate policy practices; production function; fixed effect; organisational practices